Growing Our Roots: Exploring the Home Language and Literacy Environment within the Context of Indigenous Ways of Knowing and Being - Maplethorpe, Lois; Jang, Eunice Eunhee (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2024)
Learning to read and write is crucial for children’s success in school and in life, yet many Indigenous children encounter risk factors linked to lower school achievement. This study explored Indigenous perspectives on early language and literacy through surveys and interviews with 22 participants using Indigenous methodologies. These perspectives were compared with mainstream views to highlight cultural mismatches that lead to misinterpretations of Indigenous children’s abilities. Findings emphasize the need for culturally sensitive pedagogical practices, development of self and cultural identity, the preservation of cultural traditions, and the acknowledgment of intergenerational trauma in supporting early language and literacy.